2008
DOI: 10.1677/joe-08-0218
|View full text |Cite
|
Sign up to set email alerts
|

The role of thyroid hormone in testicular development and function

Abstract: Thyroid hormone is a critical regulator of growth, development, and metabolism in virtually all tissues, and altered thyroid status affects many organs and systems. Although for many years testis has been regarded as a thyroid hormone unresponsive organ, it is now evident that thyroid hormone plays an important role in testicular development and function. A considerable amount of data show that thyroid hormone influences steroidogenesis as well as spermatogenesis. The involvement of tri-iodothyronine (T 3 ) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 236 publications
(187 citation statements)
references
References 205 publications
(247 reference statements)
5
151
0
13
Order By: Relevance
“…Erectile dysfunction and loss of libido or impotence are not uncommon in males with thyroid dysfunctions (13,67). Carani and cols., conducting a clinical trial that evaluated 34 patients with hyperthyroidism and 14 with hypothyroidism, both initiated in adulthood, demonstrated that 12,8% of these men showed some degree of sexual function deterioration (14).…”
Section: Thyroid Hormone Disorders and Male Reproductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Erectile dysfunction and loss of libido or impotence are not uncommon in males with thyroid dysfunctions (13,67). Carani and cols., conducting a clinical trial that evaluated 34 patients with hyperthyroidism and 14 with hypothyroidism, both initiated in adulthood, demonstrated that 12,8% of these men showed some degree of sexual function deterioration (14).…”
Section: Thyroid Hormone Disorders and Male Reproductionmentioning
confidence: 97%
“…The presence of iodothyronine deiodinases, enzymes that modulate the concentration, and thus the action of thyroid hormones in different tissues, were also recently identified in the rodent testis from fetal to adult life (9)(10)(11). Clinical literature indicates that most patients with thyroid hormone disorders experience some kind of sexual dysfunction, which improves or normalizes when patients become euthyroid (6,12,13). Hence, although thyroid hormone was not historically viewed as a major regulator of the male gonad, it is clear now that it has critical effects on the testis, especially during development period (14).…”
Section: Introductionmentioning
confidence: 99%
“…Positive thyroid peroxidase antibodies confirmed autoimmune thyroiditis; TPO antibody titre was 378 kU/l (normal range 0-35 kU/l). Further blood tests highlighted a raised prolactin at 1310 mU/l, deficient vitamin D (16.2 nmol/l) and a suppressed parathyroid hormone (PTH) of 7 ng/l (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), in the presence of normal calcium and phosphate. She had a raised white blood cell count of 14.9 gG/l, raised ESR and severe, hyporegenerative, microcytic anaemia (Table 2).…”
Section: Case Presentationmentioning
confidence: 99%
“…In vertebrates, D1 is mainly expressed in liver and kidney, whereas in adult mammals, the Dio1 transcripts are also identified in thyroid, pituitary gland, intestine, placenta, and gonads (St Germain & Galton 1997, Bates et al 1999, Wagner et al 2008). An interesting study that evaluated the expression profile of all three deiodinases in a wide spectrum of rat tissues showed that D1 is the only deiodinase expressed in liver, kidney, and intestine at all stages of development (Bates et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Both D1 mRNA and activity are present at low levels during fetal development and increase at later life stages, suggesting that D1 expression is regulated at least in part at a pretranslational level. The only exception for this expression pattern seems to be the testis, which presents higher levels of D1 activity in neonatal and weanling life (Bates et al 1999, Wagner et al 2008. Data on the ontogeny of the deiodinases in human fetal tissues are limited.…”
Section: Introductionmentioning
confidence: 99%